2018
DOI: 10.1016/j.nutres.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutritional supplementation with fish oil and/or leucine improves hepatic function and antioxidant defenses, and minimizes cachexia indexes in Walker-256 tumor-bearing rats offspring

Abstract: In this study, we hypothesized that throughout the pregnancy/weaning period, nutritional supplementation with leucine (which improves protein synthesis) and/or fish oil (rich in omega-3, which modulates oxidative stress) can minimize/improve cachexia-induced damage in rat offspring. Thus, we investigated the maternal supplementation with these nutrients over the modulation of cachexia index and liver function in tumor-bearing rats offspring. Pregnant rats were fed control, leucine, omega-3, and leucine/omega-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
2
3
0
2
Order By: Relevance
“…We evaluated the influence of the maternal diet on adulthood because the parameters evaluated for the dam and the weight increase in the offspring showed that the maternal diet did not affect these morphometric parameters. Additionally, the maternal leucine-rich diet did not affect tumour size, which is in accordance with previous studies [12,20], but it minimised the cancer cachexia-induced damage to the skeletal muscle, in this case the gastrocnemius tissue.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We evaluated the influence of the maternal diet on adulthood because the parameters evaluated for the dam and the weight increase in the offspring showed that the maternal diet did not affect these morphometric parameters. Additionally, the maternal leucine-rich diet did not affect tumour size, which is in accordance with previous studies [12,20], but it minimised the cancer cachexia-induced damage to the skeletal muscle, in this case the gastrocnemius tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the leucine supplementation capacity to cross de placental barrier and the ability to modify the breast milk composition [17,18,19], there is some evidence supporting the use of a maternal diet as a preventive approach. Our previous study showed that 3% leucine administered as a maternal supplement could modulate cancer cachexia-induced liver damages in tumour-bearing adult offspring [20].…”
Section: Introductionmentioning
confidence: 99%
“…Following literature data, here, we found a diminished carcass weight added to a reduction in serum albumin and total protein levels, features related to the cachexia process. These results were similar to previous studies using the same experimental model [26][27][28]. Of note, these alterations happened in both tumour-bearing groups but were more severe in WW animals, likely suggesting a higher spoliation in younger hosts, corroborating our previous report [17].…”
Section: Discussionsupporting
confidence: 92%
“…The control diet (C) contained 18% protein, of which 1.6% L-leucine, and the leucine-rich diet (L) had the same quantity of protein (18%) with the addition of 3% L-leucine (4.6% L-leucine in total). The amount of L-leucine was based on our previous experimental study [ 22 ].…”
Section: Methodsmentioning
confidence: 99%